(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article proposes cases aimed at preparing future teachers of mathematics for the formation of spatial thinking of schoolchildren in the course of geometry. The study uses empirical research methods: observation, comparison, analysis, experiment. The results of the study allow us to conclude that when preparing a mathematics student, the case method has an advantage over traditional methods of preparation. The area of application of the obtained results is the process of preparing future teachers of mathematics for the formation of students’ spatial thinking.